2009
DOI: 10.1111/j.1464-410x.2009.08526.x
|View full text |Cite
|
Sign up to set email alerts
|

Technical description and outcomes of a continuous anastomosis in open radical prostatectomy

Abstract: after ORP in the first 23 patients. The catheter was removed as soon as patients were fully mobile. A validated postal questionnaire to determine continence and its effect on quality of life was sent to all patients ≥ 3 months after ORP. RESULTSThe mean follow-up was 18 months; there were no major complications. There was an insignificant or no leak in 91% of the patients who had a cystogram. Before discharge, 33 patients reported that they were continent, whilst five required a pad(s) for stress incontinence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The BNC incidence was 2.2% (22 cases) overall, 1.4% (four) for RALP, and 2.6% (18) for ORP ( P = 0.12). Patients with BNC were diagnosed a median (range) of 4.7 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) months after surgery. At 18 months after surgery, the BNC-free rate was 97% for ORP and 99% for RALP (log-rank P = 0.13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BNC incidence was 2.2% (22 cases) overall, 1.4% (four) for RALP, and 2.6% (18) for ORP ( P = 0.12). Patients with BNC were diagnosed a median (range) of 4.7 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) months after surgery. At 18 months after surgery, the BNC-free rate was 97% for ORP and 99% for RALP (log-rank P = 0.13).…”
Section: Resultsmentioning
confidence: 99%
“…Technical factors thought to increase BNC include low surgeon volume, absence of mucosal eversion, poor vesicourethral mucosal aposition, urinary extravasation, increased blood loss, ischaemia of the bladder neck/membranous urethra, and excessive narrowing of the urethral anastomosis at the time of the procedure [3,4,6,11,12]. Some surgeons performing ORP have adopted a running anastomosis and achieved low BNC rates [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the running suture technique is theoretically more watertight, most surgeons use the interrupted technique because of the difficulty of anastomosis in open RP. Previous studies have shown that using the running suture technique for open RP is technically feasible and permits safe, early catheter removal [ 5 , 6 , 7 , 8 ]. To the best of our knowledge, this is the first study to compare perioperative outcomes of the running and interrupted techniques for RP.…”
Section: Discussionmentioning
confidence: 99%
“…The running anastomosis is theoretically more watertight and reinserting the catheter is safer and easier, because the catheter tip is less likely to pass posteriorly and extravesically [ 5 ]. Several studies have reported that running anastomosis is technically feasible and provides safe and early catheter removal in open RP [ 5 , 6 , 7 , 8 ]. However, for open RP, most surgeons perform vesicourethral anastomosis by use of interrupted sutures because of the difficulty of anastomosis and the lack of studies comparing outcomes for open RP using running and interrupted techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Anastomosis site leakage after radical prostatectomy can cause prolonged urethral catheterization periods and complications such as pelvic abscess or the collection of infected fluid [ 1 ]. Prolonged urethral catheterization causes periurethral fibrosis and stricture [ 2 , 3 ], while postprostatectomy incontinence (PPI) can be considered a complication of anastomosis site leakage.…”
Section: Introductionmentioning
confidence: 99%